2008
DOI: 10.1093/hmg/ddn093
|View full text |Cite
|
Sign up to set email alerts
|

Genetic interaction between Bardet-Biedl syndrome genes and implications for limb patterning

Abstract: Bardet-Biedl syndrome (BBS) is a pleiotropic, genetically heterogeneous disorder characterized by obesity, retinopathy, polydactyly, cognitive impairment, renal and cardiac anomalies, as well as hypertension and diabetes. Multiple genes are known to independently cause BBS. These genes do not appear to code for the same functional category of proteins; yet, mutation of each results in a similar phenotype. Gene knockdown of different BBS genes in zebrafish shows strikingly overlapping phenotypes including defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
120
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(129 citation statements)
references
References 62 publications
9
120
0
Order By: Relevance
“…Size exclusion chromatography was performed using Superose-6 10/300 GL column (GE Healthcare). MO injection and analysis of KV and melanosome transport in zebrafish was performed as previously described (14,15). For details, please see SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Size exclusion chromatography was performed using Superose-6 10/300 GL column (GE Healthcare). MO injection and analysis of KV and melanosome transport in zebrafish was performed as previously described (14,15). For details, please see SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…We previously demonstrated that knockdown of BBS genes results in the reduction or loss of Kupffer's vesicle (KV) and delays in melanosome transport. These phenotypes are shared among all BBS genes tested (14,15,31). To test whether knockdown of cct genes in zebrafish results in these BBS phenotypes, we designed anti-sense morpholino oligonucleotides (MOs) directed against the cct1, cct2 and cct3 transcription start sites.…”
Section: Requirement Of Chaperonin-like Bbs Proteins For Bbsome Assemmentioning
confidence: 99%
See 1 more Smart Citation
“…Laterality defects are also present owing to shorter motile primary cilia in the Kupffer vesicle, an embryonic organ required for left-right asymmetry [129]. Such defects also occur in CEP290-and BBS4-depleted zebrafish, with the former exhibiting additional retinal anomalies [130,131]. Ofd1 is located on the X chromosome both in mice and humans.…”
Section: Ciliopathies (A) Primary Cilia Formation and Centriolar Satementioning
confidence: 99%
“…Post axial Polydactyly: Polydactyly may involve all the four limbs, the hands or the feet alone approximately in 21% of cases. Aberrant Sonic-hedgehog signalling has been suggested to account for features of polydactyly of BBS [11]. 3.…”
Section: Retinal Dystrophy: Rod-cone Dystrophy (Atypicalmentioning
confidence: 99%